Quantitative Measurements of LRRK2 in Human Cerebrospinal Fluid Demonstrates Increased Levels in G2019S Patients - Mabrouk, Omar S.; Chen, Siwei; Edwards, Amanda L.; Yang, Minhua; Hirst, Warren D.; Graham, Danielle L. (Frontiers in Neuroscience, 2020)
Leucine-rich repeat kinase 2 (LRRK2) mutations are among the most significant genetic risk factors for developing late onset Parkinson’s disease (PD). To understand whether a therapeutic can modulate LRRK2 levels as a potential disease modifying strategy, it is important to have methods in place to measure the protein with high sensitivity and specificity. To date, LRRK2 measurements in cerebrospinal fluid (CSF) have used extracellular vesicle enrichment via differential ultracentrifugation and western blot detection. Our goal was to develop a methodology which could be deployed in a clinical trial, therefore throughput, robustness and sensitivity were critical. To this end, we developed a Stable Isotope Standard Capture by Anti-peptide Antibody (SISCAPA) assay which is capable of detecting LRRK2 from 1 ml of human CSF. The assay uses a commercially available LRRK2 monoclonal antibody (N241A/34) and does not require extracellular vesicle enrichment steps. The assay includes stable isotope peptide addition which allows for absolute quantitation of LRRK2 protein. We determined that the assay performed adequately for CSF measurements and that blood contamination from traumatic lumbar puncture does not pose a serious analytical challenge. We then applied this technique to 106 CSF samples from the MJFF LRRK2 Cohort Consortium which includes healthy controls, sporadic PD patients and LRRK2 mutation carriers with and without PD. Of the 105 samples that had detectable LRRK2 signal, we found that the PD group with the G2019S LRRK2 mutation had significantly higher CSF LRRK2 levels compared to all other groups. We also found that CSF LRRK2 increased with the age of the participant. Taken together, this work represents a step forward in our ability to measure LRRK2 in a challenging matrix like CSF which has implications for current and future LRRK2 therapeutic clinical trials.